Determinantes da expans\~ao do emprego formal: O que explica o aumento do tamanho médio dos estabelecimentos? - Carlos Henrique L. Corseuil; Rodrigo L. Moura; Lauro Ramos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The main goal of this paper is to analyze the increase of Brazilian formal employment growth rate in the last decade. The evidence suggests that this acceleration is due to a reversal in the trend of the average number of employees per establishment. More detailed investigations show evidence that this result is not derived from changes in industry composition that favors sectors with larger scales of operation, or a deepening of the process of selection, which penalizes the smaller establishments. As a matter of fact the selection component would have contributed to a decrease in the average firm size, but this effect was counterbalanced by a higher initial employment level in the most recent firms cohort.
Keywords: J21; 330; Erwerbstätigkeit; Betriebsgröße; Brasilien